Pamana [videorecording] - Cuaresma, Joe Fernandez; Iglesias, Roy C.; Ongkeko, Ellen; Zialcita, Fernando N.; Philippines. National Commission for Culture and the Arts. ([Manila] NCCA, 1995)
A tele-movie on ancestral houses and their importance and significance in Philippine culture. Features well-known actors and actresses.
VHS.
Cherry Pie Picache, Joel Torre, Allan Paule, Rolando Tinio, Rowena Basco and Perla Bautista.
Keywords: Architecture, Domestic -- Philippines; Dwellings -- Philippines